Complete Denture Education in U.S. Dental Schools - Vicki C. Petropoulos, DMD, MS;1 and Behnoush Rashedi, DMD, MSEd, MS2 (Journal of Prosthodontics, 2005)
In 2001, a survey of U.S. dental schools was conducted to determine curricular content, teaching philosophies, and techniques used in clinical complete denture programs.